2017
DOI: 10.1002/pc.24421
|View full text |Cite
|
Sign up to set email alerts
|

Acrylonitrile butadiene styrene composites reinforced with nanozirconia and PTFE: Mechanical and thermal behavior

Abstract: Acrylonitrile butadiene styrene composites reinforced with varying contents of PTFE and nanozirconia have been prepared by employing twin screw extrusion technique followed by compression molding. Mechanical properties such as hardness, tensile strength, tensile modulus, elongation at break, impact strength, flexural strength, and flexural modulus have been determined by conducting various mechanical tests according to corresponding ASTM test standards. Thermogravetic analysis (TG/DTA) has been carried out so … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…Therefore, more POM chains can be constrained surrounding PTFE particles, 34 thereby leading to a relatively higher flexural strength. Similarly, Amrishraj and Senthilvelan 35 reported that both the tensile strength and flexual strength decreased with the addition of PTFE in acrylonitrile butadiene styrene. The soft nature of PTFE fillers as well as the incompatibility between PTFE and the host matrix are believed to be the contributing factors.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Therefore, more POM chains can be constrained surrounding PTFE particles, 34 thereby leading to a relatively higher flexural strength. Similarly, Amrishraj and Senthilvelan 35 reported that both the tensile strength and flexual strength decreased with the addition of PTFE in acrylonitrile butadiene styrene. The soft nature of PTFE fillers as well as the incompatibility between PTFE and the host matrix are believed to be the contributing factors.…”
Section: Resultsmentioning
confidence: 86%
“…This can be ascribed to the fact that the presence of soft PTFE fibers would absorb a great amount of energy by fiber breakage/pullout when the composite is subjected to external impact. 35 Additionally, the shape deformation or cracking of surrounding matrix will contribute to the increase of impact strength. However, the impact strength for POM/particle composites decreased with an increase of filler concentration, which is attributed to the poor interfacial interaction between PTFE particles and POM, as mentioned previously.…”
Section: Resultsmentioning
confidence: 99%
“…The char yield of the filled composites increases from 32% (unfilled compound) to 37-45%. At the same temperature, the LOI values (32)(33)(34)(35) of the filled composites are also found to be appreciably higher than that (30) of unfilled compound. This definitely indicates improvement in flame retardancy of the CR composites brought by incorporation of zirconia and that is little better for in situ zirconia in comparison to externally filled zirconia.…”
Section: Paper Materials Advancesmentioning
confidence: 78%
“…Parera et al 31 incorporated in situ zirconia in natural rubber to improve the hardness and abrasion resistance of the composites. Amrishraj et al 32 studied the mechanical, thermoelastic and thermal properties of acrylonitrile butadiene styrene composites filled with PTFE (poly tetrafluoroethylene) and nano-zirconia. Addition of zirconia was found to improve the mechanical properties, thermal stability and viscous behaviour of composites in this work.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that the thermal stability, storage modulus, tensile strength, and flexural strength are improved. However, the damping properties are reduced due to the addition of nano zirconia [2]. Investigation results revealed that the inclusion of graphite in ABS material lowers the mechanical properties.…”
Section: Introductionmentioning
confidence: 99%